Ability of global climate models at a regional scale over Australia. (6th December 2007) - Perkins, Sarah E.; Pitman, Andy J.; Holbrook, Neil J.; McAneney, John
We evaluate the coupled climate models used in the fourth assessment report of the Intergovernmental Panel on Climate Change (IPCC). Our evaluation is focused on twelve regions of Australia for the daily simulation of precipitation, minimum temperature and maximum temperature. We base our evaluation on Probability Density Functions (PDFs). We introduce a simple quantitative measure of how well each climate model can capture the observed PDFs for each variable over Australia. Across all three variables, the coupled climate models perform better than we expected although one model is clearly flawed in simulating maximum temperature. An overall ranking of the climate models, for the three variables is presented. We therefore provide guidance on those climate models that are skillful over Australia, providing direction on those that should be used in impacts assessments where those impacts are based on precipitation or temperature.